Di(ethylene glycol) methyl ether methacrylate (DEGMEMA)-derived gels align small organic molecules in methanol - García, Manuela Emila (2017)
Residual dipolar couplings (RDCs) constitute an important NMR parameter for structural elucidation in all areas of chemistry. In this study, di(ethylene glycol) methyl ether methacrylate (DEGMEMA)-basedgelsare introduced as alignment media for the measurement of RDCs of small organic molecules in polar solvents such as methanol. The low viscosity of methanol permits the execution of J-scaled BIRD HSQC experimentsthat yield very sharp lines in anisotropic conditions. The gels have excellent mechanical properties, and their compression and expansion in the swollen state can be reversed and performed multiple times. This process enables the easy loading and release of analytes. The excellent performance of these new aligning gels is demonstrated by analyzing the structure of the alkaloid retrorsine.